Recluce tales : stories from the world of Recluce - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce, 2017)
A collection of short stories set in the world of the Recluce saga features seventeen new tales and four popular reprints spanning the thousand-year history of Recluse, in an anthology complemented by a background essay.